2018
DOI: 10.1096/fj.201800943r
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of pituitary gonadotropes to hyperglycemia leads to epigenetic aberrations and reduced follicle‐stimulating hormone levels

Abstract: The connection between metabolism and reproductive function is well recognized, and we hypothesized that the pituitary gonadotropes, which produce luteinizing hormone and follicle-stimulating hormone (FSH), mediate some of the effects directly via insulin-independent glucose transporters, which allow continued glucose metabolism during hyperglycemia. We found that glucose transporter 1 is the predominant glucose transporter in primary gonadotropes and a gonadotrope precursor-derived cell line, and both are res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 69 publications
(115 reference statements)
0
11
0
Order By: Relevance
“…5 B) and LβT2 cells, we performed expression profiling of Slc2a 1–10, and 12 mRNA and demonstrate that like LβT2 cells, Slc2a1 is the most highly expressed glucose transporter in primary gonadotropes in female mice (Fig. 6 D and 13 ). Importantly, we found that primary gonadotropes exhibit the same Slc2a expression profile as LβT2 cells, though at a higher level.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…5 B) and LβT2 cells, we performed expression profiling of Slc2a 1–10, and 12 mRNA and demonstrate that like LβT2 cells, Slc2a1 is the most highly expressed glucose transporter in primary gonadotropes in female mice (Fig. 6 D and 13 ). Importantly, we found that primary gonadotropes exhibit the same Slc2a expression profile as LβT2 cells, though at a higher level.…”
Section: Resultsmentioning
confidence: 88%
“…Our data in the LβT2 cell line provide evidence that gonadotropes sense glucose and can integrate this information to alter hormone production. Although primary gonadotropes are glucose responsive 13 , to date, no functional protein or metabolic assays have been performed on primary gonadotropes to verify glucose sensing. To answer the question of whether primary gonadotropes respond to GnRH by inducing glycolysis, we devised a protocol to obtain and culture purified primary gonadotropes, a prerequisite for XF analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For transcriptome analysis, RNA was extracted from the mice ovaries and purified as above, and sequenced by CEL-seq, using Illumina HiSeq 2500 at the Technion Genome Center (as in 44 ). FastQC was used for quality control and the reads were mapped by TopHat algorithm to mm10 genome assembly.…”
Section: Quantitative Pcr Transcriptome and Methylation Analysismentioning
confidence: 99%